2013
DOI: 10.3855/jidc.2711
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug resistance profiles and the genetic features of Acinetobacter baumannii isolates from Bolivia

Abstract: Introduction: Acinetobacter baumannii is opportunistic in debilitated hospitalised patients. Because information from some South American countries was previously lacking, this study examined the emergence of multi-resistant A. baumannii in three hospitals in Cochabamba, Bolivia, from 2008 to 2009. Methodology: Multiplex PCR was used to identify the main resistance genes in 15 multi-resistant A. baumannii isolates. RT-PCR was used to measure gene expression. The genetic environment of these genes was also anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The most prevalent ESBL gene was bla TEM , which was detected in 35 (87.5%) isolates; however, bla SHV and bla VEB genes were not found [ 29 ]. Moreover, in the study by Lopes et al, the PCR technique performed to detect beta-lactamase genes in 50 isolates showed that all isolates harbored the bla TEM gene, while bla SHV and bla VEB genes were not found in any of the strains [ 38 ]. The results of these studies regarding the prevalence of bla T EM , bla T EM and bla VEB ESBL genes were similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent ESBL gene was bla TEM , which was detected in 35 (87.5%) isolates; however, bla SHV and bla VEB genes were not found [ 29 ]. Moreover, in the study by Lopes et al, the PCR technique performed to detect beta-lactamase genes in 50 isolates showed that all isolates harbored the bla TEM gene, while bla SHV and bla VEB genes were not found in any of the strains [ 38 ]. The results of these studies regarding the prevalence of bla T EM , bla T EM and bla VEB ESBL genes were similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…The aac-6 -Ib class of aminoglycoside inactivating enzymes has been shown to confer resistance to tobramycin, dibekacin, amikacin, 5-episisomicin, netilmicin, 2 -Nethylnetilmicin and sisomicin (Lopes et al, 2013). Researchers from Turkish University Hospital had previously reported the presence of bla GES-22 gene in eight of their extensively drug resistant A. baumannii isolates (Cicek et al, 2014).…”
Section: Isolatementioning
confidence: 97%
“…PCR was performed on all isolates as described earlier on all isolates to identify insertion elements causing disruption of the carO gene (29 kDa outer membrane protein) which leads to carbapenem resistance (Mussi et al, 2005). Additionally, primers FU and RU were used for amplification of the intergenic region upstream of the bla ADC gene and primers FD and RD were used to amplify the intergenic region downstream of the bla ADC gene (Lopes et al, 2013). The quinolone resistance mediating genes gyrA and parC were analysed for presence of mutations by PCR and sequencing as described previously (Lopes et al, 2013).…”
Section: Screening For Presence Of Antibiotic Resistance Genesmentioning
confidence: 99%
See 2 more Smart Citations